Antitumor effect of antitissue factor antibody‐MMAE conjugate in human pancreatic tumor xenografts. Issue 6 (9th March 2015) - Koga, Yoshikatsu; Manabe, Shino; Aihara, Yoshiyuki; Sato, Ryuta; Tsumura, Ryo; Iwafuji, Hikaru; Furuya, Fumiaki; Fuchigami, Hirobumi; Fujiwara, Yuki; Hisada, Yohei; Yamamoto, Yoshiyuki; Yasunaga, Masahiro; et al.
<x xml:space="preserve">Abstract</x> Tissue factor (TF) triggers the extrinsic blood coagulation cascade and is highly expressed in various types of cancer. In this study, we investigated the antitumor effect of an antibody–drug conjugate (ADC) consisting of an anti‐TF monoclonal antibody and monomethyl auristatin E (MMAE). MMAE was conjugated to an anti‐human TF or anti‐mouse TF antibody using a valine‐citrulline linker that could be potentially hydrolyzed by cathepsin B in the acidic environment of the lysosome. The cytotoxic and antitumor effects of the ADCs against four pancreatic cancer cell lines were analyzed. Both the ADC with the anti‐human TF antibody and that with the anti‐mouse TF antibody were stable under physiological conditions. The anti‐human ADC was internalized in TF‐expressing human tumor cell lines, followed by effective MMAE release. The half maximal inhibitory concentration (IC50) of MMAE was approximately 1 nM for all of the cell lines used. Meanwhile, the IC50 of anti‐human ADC was 1.15 nM in the cell lines showing high TF expression, while exceeding 100 nM in the cells showing low TF expression levels. Anti‐human ADC with passive and active targeting ability exerted significant suppression of tumor growth as compared to that observed in the saline group (p < 0.01). Also significant tumor growth suppressions were seen at the anti‐mouse ADC and control ADC groups compared to the saline group (p < 0.01) due to EPR effect. Because various clinical human cancers express highly amount of TF, this new anti‐TF ADC may deserve a clinical evaluation.